The impact of CEO characteristics on the international entrepreneurship of small island- based firms - Guido Rojer, Jr.; Watkins-Fassler, Karen; de Juan, R.; Rai, Anoop (Island Studies Journal, 2023)
This paper examines the impact of CEO characteristics on the International Entrepreneurship (IE) of listed island-based firms (IBFs) during the period 2009-2018. The research considers 164 companies from a sample of eight small islands with securities exchanges including more than one firm headquartered on the island. The selected islands are: Barbados, Cyprus, Fiji, Iceland, Jamaica, Malta, Mauritius, and Trinidad & Tobago. Framed on the upper echelons theory and social network theory, the influence on IE of CEO's tenure, academic background and achievement, family allegiance, and international exposure is studied, taking into account the small island particularities. Through a binary probit model, it is concluded that CEOs' family allegiance, tenure, and academic background (if the CEO majored in Business Administration, Finance, Accounting, or Economics) are negatively related with IE, while CEOs' academic achievement and international exposure are positively associated with IE. Some of these results are atypical in the existing literature; nevertheless, islandness can explain these results. The conclusions attained suggest new theoretical and empirical lines of IE research for IBFs.
Keywords: Chief Executive Officers (CEOs); International Entrepreneurship (IE); island-based firms; small islands; social network theory; upper echelons theory; JCR; Scopus